Knowledge of Early Marriage Risks among Senior High School Students in Pulang Pisau Regency: A Descriptive Analysis - Heti Mariani; Itma Annah; Happy Marthalena Simanungkalit; Greiny Arisani (SIGn Journal of Public Health, 2025)
Early marriage in the rural areas of Central Kalimantan remains a persistent threat to the reproductive health and psychosocial stability of adolescents. This study aims to conduct a descriptive analysis of knowledge levels regarding early marriage risks among senior high school students in Pulang Pisau Regency, focusing on mapping respondents’ sociodemographic profiles. The study employed a quantitative descriptive design. Sampling was conducted using a purposive technique involving 70 respondents from a population of 174 students at SMAN 2 Kahayan Tengah. Primary data collection used a closed-ended questionnaire tested for validity and reliability, which was analyzed univariately using frequency distributions and percentages. The results showed that the majority of respondents possessed a knowledge level in the good category (52.86%). A good level of understanding was predominantly found among female adolescents (68.57%), respondents with parents having a higher education (83.33%), the family group with an income below the minimum wage threshold (55.10%), and respondents without a history of early marriage in their family structure (54.54%). Novel findings of this research revealed that non-mass media information channels relying on interpersonal communication interactions from teachers, health workers, and family were the most dominant and effective educational tools (58.06%). In conclusion, adolescents’ high cognitive ability serves as strong social capital. Family education levels and interpersonal communication played a much more significant role than economic income levels. As a policy implication, health promotion interventions in schools need to be revitalized by positioning educators and peer cadres as the primary drivers of early marriage prevention education.